Identification of QTL for reaction to three races of Colletotrichum trifolii and further analysis of inheritance of resistance in autotetraploid lucerne - Mackie, J.; Musial, J.; Armour, D.; Phan, H.; Ellwood, Simon; Aitken, K.; Irwin, J. (Springer, 2007)
Anthracnose, caused by Colletotrichum trifolii, is one of the most serious diseases of lucerne worldwide. The disease is managed through deployment of resistant cultivars, but new pathotypes present a challenge to the successful implementation of this strategy. This paper reports the genetic map locations of quantitative trait loci (QTL) for reaction to races 1, 2 and 4 of C. trifolii in a single autotetraploid lucerne clone, designated W126 from the Australian cv. Trifecta. Resistance was mapped in a backcross population of 145 individuals, and reaction was assessed both by spray and injection inoculation of stems. Resistance to injection inoculation with races 1 and 4 was incompletely dominant and closely linked (phenotypic markers 2.2 cM apart); these resistances mapped to a linkage group homologous to Medicago truncatula linkage group 8. When the spray inoculation data were subjected to QTL analysis, the strongest QTL for resistance was located on linkage group 8; six QTL were identified for race 1 and four for race 4. Resistance to race 2 was incompletely recessive; four QTL were identified and these include one QTL on linkage group 4 that was also identified for race 1. Modelling of the interactions between individual QTL and marker effects allowed a total of 52–63% of the phenotypic variation to be described for each of the different races. These markers will have value in breeding lucerne, carrying multiple sources of resistance to the three known races of C. trifolii.